1991
DOI: 10.1159/000125795
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Intestinal Peptide in the Hypothalamus and Pituitary

Abstract: Data are presented to show that vasoactive intestinal peptide (VIP) is synthesized and secreted by the hypothalamus and anterior pituitary and that it participates in the regulation of pituitary functions. Immunoreactive VIP in the hypothalamus and pituitary is increased following estrogen treatment and adrenalectomy and is reduced in hyperprolactinemic states. The level of VIP mRNA in the hypothalamus is increased during lactation and sexual maturation, while that in the anterior pituitary shows a sexual dimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 31 publications
2
24
1
1
Order By: Relevance
“…Conversely, passive immunoneutralization with VIP antisera reduces or abolishes the normal PRL surge associated with ether stress, suckling, and direct serotonergic stimulation (Shimatsu et al, 1984;Abe et al, 1985) and (Kaji et al, 1985). Afferent sources of VIP include the suprachiasmatic nucleus (SCN) and the PVN (Lam, 1991). However, VIP immunoreactive granules have also been localized in the lactotrophs (Segerson et al, 1989;Morel et al, 1982).…”
Section: Prl Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, passive immunoneutralization with VIP antisera reduces or abolishes the normal PRL surge associated with ether stress, suckling, and direct serotonergic stimulation (Shimatsu et al, 1984;Abe et al, 1985) and (Kaji et al, 1985). Afferent sources of VIP include the suprachiasmatic nucleus (SCN) and the PVN (Lam, 1991). However, VIP immunoreactive granules have also been localized in the lactotrophs (Segerson et al, 1989;Morel et al, 1982).…”
Section: Prl Stimulationmentioning
confidence: 99%
“…Consequently, the PVN is among the best-studied sites of serotonininduced PRL release, and is known to contain the Recruitment of VIP neurons in the serotonin-induced PRL response is implied by the fact that VIP antiserum significantly blunts the usual PRL surge associated with serotonergic stimulation in vivo (Kaji et al, 1985;Shimatsu et al, 1982,). While it is hypothesized that VIP neurons of the PVN are directly stimulated by serotonergic fibers (Kiss et al, 1984;Lam, 1991;Reichlin, 1988), to date, serotonergic terminals have not been demonstrated on these VIPexpressing cells (Kiss et al, 1984).…”
Section: Modulatorsmentioning
confidence: 99%
“…During the last decade, it has also been suggested that VIP could act as a neuroendocrine hormone (Lam 1991). Accordingly, studies have revealed a physiological role for VIP in reproductive functions.…”
Section: Introductionmentioning
confidence: 99%
“…Extending the duration of feed availability to 24 h from the 8 h used in previous experiments appeared to reduce the likelihood of observing an effect of the brief, intermittent infusions of VIP on DMI. There is evidence that VIP stimulates the secretion of prolactin, growth hormone, and thyroid hormone (Zudenigo and Lackovic 1989;Lam 1991), and relaxes the ROO and, therefore, has the potential to stimulate feeding in a complex way including via the central release of important hormones and/or via a local effect on the reticulorumen motility. It is not clear whether the VIP level in the general circulation would be high enough to induce any effects on a central ingestion center at the current infusion rate.…”
Section: Effects Of Vipmentioning
confidence: 99%